Preparation, characterization and photocatalytic activity of silver doped zinc oxide photocatalysts - Rasouli, Elisa (2014)
In this study, silver doped zinc oxide and undoped zinc oxide photocatalysts were synthesized through precipitation-irradiation method. In order to evaluate the effect of irradiation time during synthesis, the photocatalysts were prepared at different irradiation duration of 12, 24 and 48 hours. The effect of Ag on the properties and photocatalytic performance of ZnO was also evaluated by preparing Ag-doped ZnO catalyst with different silver loading from 1 to 3 wt%. The resulting catalysts were characterized by X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM), Total surface Area Measurement (BET Method) and Band Gap Measurement. XRD patterns showed hexagonal structure of zinc oxide. FESEM results confirmed hexagonal structure of zinc oxide and also showed flake morphology with increasing irradiation time. However, both FESEM and TEM images showed high agglomerated particles but it should be noticed that agglomeration decreased with increasing irradiation time. In addition, increasing silver percentage doped on zinc oxide decreased the flake morphology and led to more agglomerated particles. The surface area of ZnO decreases with increasing irradiation time and with addition of Ag. The band gap energy of the ZnO remained constant with increasing radiation time but increased with the addition of 2 wt. % Ag. Due to high agglomeration, measurement of photocatalysts particle size was not conducted. The efficiency of produced ZnO and Ag doped ZnO was examined for degradation of Methyl orange as a model of pollutant under UV-irradiation. Influence of different parameters on degradation performance of Methyl orange such as mass of catalyst, initial concentration of dye, and initial pH were tested. The results showed that the efficiency of catalyst decreased with increasing irradiation time. It was observed that the removal percentage of dye increased with increasing silver loading on zinc oxide and the mass of catalysts up to an optimum amount. Furthermore, the maximum removal percentage was achieved at pH 5. In conclusion, the highest photodegradation activity of 81% of 10 ppm MO was achieved using 0.8 g of 2% Ag/ZnO catalyst at pH 5.